DOI: 10.14264/uql.2015.752
|View full text |Cite
|
Sign up to set email alerts
|

Kinship and sociability in eastern grey kangaroos

Abstract: School of Biological Sciencesii Frontispiece: A family group of eastern grey kangaroos at the Wilsons Promontory National Park in February, 2010, consisting of (left to right) adult female #6 (carrying a 3-month-old pouch young daughter that became #223), adopted young-at-foot daughter #116 (still suckling at approximately 15 months) and sub-adult daughter #7 of approximately 26 months. Photo by Wendy J. King.iii Abstract Animal grouping patterns are generally shaped by ecological constraints such as resource … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 131 publications
(215 reference statements)
0
3
0
Order By: Relevance
“…However, since annual rainfall is predicted to affect multiple aspects of the kangaroos’ behaviour, this was not unexpected, and we included year as a control variable in the models. Some social network metrics are expected to increase with observation frequency in networks where not every individual is observed in each sampling period [ 58 ], and indeed this correlation between sample size and social network metrics has been described in another population of eastern grey kangaroos [ 59 ]. For the females included in our analyses (individuals with a minimum of 10 observations per year at a frequency of at least once per two months), strength but not clustering coefficient was significantly correlated with the number of sightings (strength: Spearman rank correlation: S = 1 847 800, ρ = 0.470, p < 0.001; clustering coefficient: Spearman rank correlation: S = 39 87 700, ρ = −0.036, p = 0.547); we thus included observation frequency as an explanatory variable in all models to control for this effect.…”
Section: Methodsmentioning
confidence: 99%
“…However, since annual rainfall is predicted to affect multiple aspects of the kangaroos’ behaviour, this was not unexpected, and we included year as a control variable in the models. Some social network metrics are expected to increase with observation frequency in networks where not every individual is observed in each sampling period [ 58 ], and indeed this correlation between sample size and social network metrics has been described in another population of eastern grey kangaroos [ 59 ]. For the females included in our analyses (individuals with a minimum of 10 observations per year at a frequency of at least once per two months), strength but not clustering coefficient was significantly correlated with the number of sightings (strength: Spearman rank correlation: S = 1 847 800, ρ = 0.470, p < 0.001; clustering coefficient: Spearman rank correlation: S = 39 87 700, ρ = −0.036, p = 0.547); we thus included observation frequency as an explanatory variable in all models to control for this effect.…”
Section: Methodsmentioning
confidence: 99%
“…Our preliminary analysis showed that raw social network metrics were highly influenced by sighting frequency (Spearman's rank correlations, transitivity: rho = -0.70, S = 1035690000, P < 0.01, betweenness: rho = 0.74, S = 25780000, P < 0.01). A similar trend has been observed in eastern grey kangaroos, which display a similarly high level of fission-fusion dynamics (King, 2015). We chose to analyse gregariousness and social network metrics only for individuals seen eight or more times in a given period, which maximised the number of individuals in our analysis and minimised the chance of producing inaccurate results from including individuals with low numbers of samples.…”
Section: Calculation Of Individuals' Sociability Metricsmentioning
confidence: 78%
“…Connections can also change temporally, as is the nature of a dynamic society (Castles et al, 2014). Further, metrics are rarely comparable between populations of different sizes (Faust & Skvoretz, 2002;James, Croft, & Krause, 2009) and recent work has suggested that individual metrics are heavily influenced by sample sizes (King, 2015). For example, an individual sampled 40 times is likely to have more connections than an individual sampled 10 times as an artefact of the sampling, rather than being biologically relevant.…”
Section: Quantifying Sociabilitymentioning
confidence: 99%